A case study exploring the experience of graduate entry nursing students when learning in practice - Stacey, Gemma; Pollock, Kristian; Crawford, Paul (Wiley, 2015)
Aim. To explore how Graduate Entry Nursing students present and position themselves in practice in response to anti-intellectualist stereotypes and assessment structures. Background. A complex background turbulence exists in nurse education which incorporates both pro- and anti-intellectualist positions. This represents a potentially challenging learning environment for students who are recruited onto pre-registration programmes designed to attract graduates into the nursing profession on the basis of the specific attributes they bring known as ‘graduateness’. Design. A longitudinal qualitative case study conducted over 2 years. Methods. Data were collected from eight Graduate Entry Nursing students at 6 monthly points between 2009–2011 via diaries, clinical assessment documentation and interviews. Forty interviews took place over 2 years. Additionally, three focus groups involving 12 practice assessors were conducted at the end of the study period. Data were analysed through a social constructivist lens and compared with a set of suppositions informed by existing empirical and theoretical debates. Findings. Demonstrated the interplay of performance strategies adopted by Graduate Entry Nursing students to challenge or pre-empt actual or perceived negative stereotypes held by established practitioners to gain acceptance, reduce threat and be judged as appropriately competent. Conclusion. Students interpreted and responded to, perceived stereotypes of nursing practice they encountered in ways which facilitated the most advantageous outcome for themselves as individuals. The data present the creative and self-affirming strategies which students adopted in response to the expectations generated by these stereotypes. They also depict how such strategies commonly involved suppression of the attributes associated with ‘graduateness’.